Analisis Pemanfaatan Jaringan Politik Firdaus dalam Pemilihan Umum Legislatif Tahun 2019 di Sumatera Barat - Hafiz Satria Putra; Asrinaldi Asrinaldi; Indah Adi Putri (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This journal explains how the optimization of political networks is carried out by candidates for DPRD members of West Sumatra Province during the general election, especially the 2019 legislative election. The election system which is based on an open system is not uncommon for each contestant to take advantage of several ways to make it easier for each candidate to be able to reach existing constituents in each area within his constituency. In this research using descriptive qualitative research method with an instrumental case study approach, data collected using in-depth interview techniques along with collecting documentation and related to this research as well as observation. Researchers use political networks as the basis of this research. The results of this study indicate that the optimization of political networks used by candidates is based on the activities of candidates from being a student to becoming a member of the Provincial DPRD. With activities like that the activation of political networks is built to be able to make capital for candidates to be able to advance in the general election, then political messages that are structured on political networks and political narrative stages that are obtained by candidates become one of the important aspects of their election as members DPRD of West Sumatra Province.Keywords: Political Networks; Legislative Elections; Firdaus AbstrakJurnal ini menerangkan bagaimana pengoptimalan jaringan politik yang diimplementasikan calon anggota DPRD Provinsi Sumatera Barat disaat pemilihan umum khususnya pemilihan legislatif tahun 2019. sistem pemilu yang berazaskan pada sistem terbuka tidak jarang setiap kontestan untuk memanfaatkan beberapa cara agar dapat memudahkan setiap kandidat untuk bisa menjangkau konstituen yang ada disetiap daerah yang beradap di daerah pemilihannya. Dalam penilitian ini menggunakan metode penilitian kualitatif deskriptif dengan pendekatan studi kasus instrumental, data yang dikumpulkan menggunakan teknik wawancara yang mendalam beserta pengumpulan dokumentasi dan terkait penelitian ini sekaligus observasi. Peneliti memakai jaringan politik sebagai landasan penelitian ini. Hasil penelitian ini menunjukan bahwa pengoptimalan jaringan politik yang dipakai oleh kandidat di dasari adanya aktivitas kandidat sejak mahasiswa sampai menjadi anggota DPRD Provinsi. Adanya aktivitas seperti itu aktivasi jaringan politik terbangun untuk bisa menjadikan modal bagi kandidat untuk dapat melaju pada pemilihan umum tersebut, selanjutnya pesan politik yang terstruktur pada jaringan politik maupun politik panggung narasi yang di dapatkan oleh kandidat menjadi salah satu aspek penting atas keterpilihannya menjadi salah satu anggota DPRD Provinsi Sumatera BaratKata Kunci: Jaringan Politik; Pemilihan Legislatif; Firdaus